Effect of vision training on batting performance and pitch recognition of Division I baseball players - Gilliam, S. T.; Szymanski, D. J.; Braswell, M. T.; Britt, A. T.; Cicciarella, C. F.; Herring, A. L.; Holloway, B. T.; Lowe, H. E.; Potts, J. D.; Szymanski, J. M.; Till, M. E.; Spaniol, F. J. (The Journal of Strength and Conditioning Research, 2010)
To investigate the effect of preseason vision training on bat velocity (BV), batted-ball velocity (BBV), and pitch recognition (PR). Twenty-one male NCAA Division I baseball players (age = 20.3 + 1.0 yr) were randomly assigned to 1 of 2 groups 6 weeks before the season began. Group 1 (n = 10) was the control group and received no vision training. Group 2 (n = 11) completed 18 vision training sessions over 6 weeks (3 sessions/wk). Vision exercises consisted of visual flexibility (convergence and divergence), visual recognition (accuracy and response time), and visual tracking (accuracy and response time). Each session was performed with a game pad controller connected to a computer and lasted between 10-20 minutes. Before beginning the 6-week vision training program, all subjects were tested on body composition using a TanitaTM bioelectrical impedance device; grip strength using a Jamar(TM) hand dynamometer; and vertical jump using a Vertec(TM) vertical jump apparatus to assess leg power. Instantaneous BV was recorded by a SETPRO SPRT5ATM chronograph. BBV was measured by a Stalker ProTM radar gun set up behind home plate while subjects hit balls, delivered at a mean velocity of 29.1 m/s (65 mph) from the Hack-AttackTM pitching machine (set-up 13.7 m or 45 ft away from home plate), between a target zone set up in a batting cage. A delivered ball from that distance is equivalent to a 38.9 m/s (87 mph) fastball. Subjects also performed PR where a baseball was delivered at a mean velocity of 38.0 m/s (85 mph) from the AtecTM automated pitching machine set-up 20.3 m (60 ft 6 in) away from home plate and called out "ball" or "strike". An official NCAA "strike zone", adjusted for each player, was set-up behind home plate for each hitter. The number of correct responses was recorded as the PR score. Both groups were also assessed by a commercial visual training program on their depth perception, visual flexibility, visual recognition, and visual tracking. Once the 6-week training program was completed, all subjects were re-tested on the same parameters previously listed. Univariate ANOVAs comparing group 1 and 2 revealed that group 2 significantly (p < 0.05) improved in convergence percentage (p = .003), visual recognition response time (p = .010), visual recognition accuracy (p = 0.034), visual tracking response time (p = .003), and PR (p = 0.028). There were no significant differences in BV, BBV, divergence, or depth perception. Data suggests that vision training can improve certain aspects of a baseball player's vision; however there was no effect on their BBV, divergence, or depth perception during the preseason. Although no significant improvements in BBV occurred for either group, group 2 significantly improved PR compared to group 1. This may allow a hitter to be more selective in the batter's box, thus increasing the possibility of being more accurate at bat-ball contact. A limitation of this study was BBV. Not all batted-balls hit within the target zone were recorded by the Stalker ProTM radar gun. It is suggested that future studies count the total number of swings taken to achieve successful BBV data to see if there is a significant difference between groups. This may provide data that demonstrates greater skill in hitting the ball "up the middle."